Desain Prototype Sistem Kendali dan Pelacakan Pada Mesin Boat - Rizky Edi Saputra; Suci Aulia; Syahban Rangkuti (Jurnal Rekayasa Elektrika, 2021)
Indonesia is an archipelago country with more than 70% of its territory consisting of water. Due to these geographical conditions, many Indonesian people rely on water transportation as a means of crossing transportation. However, many of the crossings in Indonesia still use a manual control system in determining the direction of the boat. In this study, a prototype control and tracking system designed for a boat engine can be used as an automatic control system (autopilot) in water transportation. This system is created using a waypoint control system that can navigate automatically to a predetermined location. This control system is designed with an electric control system that utilizes a microcontroller, GPS (Global Positioning System) module, and compass module as a navigation control device. From the test results, it can be concluded that the level of accuracy of the GPS coordinates reading is as far as 4.8 meters and based on the test of the waypoint navigation system , the system accuracy level is 10.8 meters.